Analgesic and Neuropharmacological Activities of Methanol Extract from the Leaf of Nicotiana plumbaginifolia Viv. (Bangladesh Pharmaceutical Journal, 2015)
The aim of study was to evaluate the analgesic and neuropharmacological activities of the leaf of Nicotiana plumbaginifolia. The central analgesic activity of the methanolic extract was evaluated in Swiss Albino mice by using tail immersion, hot plate and acetic acid-induced writhing tests at 100, 200 and 400 mg/kg body weight. These tests showed significant analgesic activity of the extract compared to the standard drug, diclofenac-Na (1 mg/kg b.w.). The neuropharmacological activities were evaluated using hole cross, open field, light/dark box and elevated plus maze stage tests in mice model at 100, 200 and 400 mg/kg body weight. The results of neuropharmacological assays demonstrated potential CNS depressant activity of the extract when compared to the standard drug, diazepam (1 mg/kg b.w.)Bangladesh Pharmaceutical Journal 18(2): 85-89, 2015